Kinerja Aparatur Dalam Pengurusan Sertifikat Tanah Di Kantor Desa Pusungi Kecamatan Ampana Tete Kabupaten Tojo Una-Una - Parebba, Miasantika I. Dg.; Tahili, Mashuri H.; Amijaya, Meldi (JPS: Journal of Publicness Studies, 2026)
This research aims to analyze the performance of the Pusungi Village apparatus, Ampana Tete District, Tojo Una-Una Regency, especially in the service of land certificate management. Performance is measured through the dimensions of productivity, service quality, responsiveness, responsibility, and accountability. The results of observations and interviews show that in general, the apparatus's performance is in the fairly good category but not yet optimal. The apparatus's productivity is hindered by limited human resources (only handled by the Government Section Head), manual administrative processes, and unprepared community documents (requiring 6-12 months for verification). Service quality still needs improvement, marked by the absence of service time standards, procedures considered complicated because information is only conveyed orally, and limited supporting facilities. In the Responsiveness dimension, the apparatus has the willingness to serve quickly, but is often hindered by high workload and the absence of written information media, causing repeated administrative problems. Responsibility shows compliance with rules, but is not yet supported by written SOPs and adequate archiving systems, making service consistency dependent on individuals. Finally, financial Accountability is assessed as good (transparent costs), but periodic information accountability is weak, causing uncertainty in completion time for the community. Overall, performance improvement requires improvements in technical, administrative, and structural aspects. Digitalization of administration, provision of standard SOPs, improvement of human resource competence through training, and development of written service information media are needed to realize faster, accurate, and efficient land certificate services.